2005
DOI: 10.1210/jc.2005-0261
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Adiponectin Responses in Overweight Inactive Elderly following Resistance Training and Detraining Are Intensity Related

Abstract: Resistance training and detraining may alter leptin and adiponectin responses in an intensity-dependent manner. Leptin and adiponectin changes were strongly associated with RMR and anthropometric changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
230
4
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(272 citation statements)
references
References 59 publications
23
230
4
6
Order By: Relevance
“…These results are in agreement with previous studies (11,19,38). Based on the negative correlation between adiponectin and body fat percentage found in the present study and to reduce the risks of atherosclerosis by reducing body fat, it could be suggested that patients and normal sedentary individuals need to participate in endurance-and resistance-training programmes that lead to loss of body weight and fat reduction.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in agreement with previous studies (11,19,38). Based on the negative correlation between adiponectin and body fat percentage found in the present study and to reduce the risks of atherosclerosis by reducing body fat, it could be suggested that patients and normal sedentary individuals need to participate in endurance-and resistance-training programmes that lead to loss of body weight and fat reduction.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, adiponectin concentration did not change following 12 weeks of circuit weight training at 50-60% 1-RM, which is a low-intensity protocol. Our findings support those of Klimcakova et al (20) and the low-intensity protocol of Fatouros et al (19). Therefore, it can be concluded that changes in adiponectin in response to resistance training might be intensity related.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fatouros and colleagues 27 examined the impact of a 48-week RET program for 50 older men and compared various intensities of training. At post-test, the researchers found that leptin was reduced in each intervention group and adiponectin was increased in the high intensity intervention group only.…”
Section: Discussionmentioning
confidence: 99%